Do detection-based warning strategies improve vehicle yielding behavior at uncontrolled midblock crosswalks?. (July 2021) - Hussain, Qinaat; Alhajyaseen, Wael K.M.; Pirdavani, Ali; Brijs, Kris; Shaaban, Khaled; Brijs, Tom
Highlights: Detection-based strategies significantly improved drivers yielding rates. LED and VMS conditions were helpful in reducing the vehicle-pedestrian conflicts. Detection-based strategies were effective in terms of drivers' speed reduction. Do detection-based warning strategies improve vehicle yielding behavior at uncontrolled midblock crosswalks? Abstract: Pedestrians being the most vulnerable road users account for a large proportion of injuries and fatalities from road traffic crashes. Pedestrians are involved in around one-third of the whole fatalities coming from the road traffic crashes in the state of Qatar. In areas with uncontrolled midblock crosswalks, it is very crucial to improve drivers' alertness and yielding behavior. The objective of this driving simulator study is to investigate the impact of pedestrian detection strategies and pavement markings on driving behavior at high-speed uncontrolled crosswalks. To this end, an untreated condition (i.e. Control) was compared with three treatment conditions. The three treated conditions included two detection strategies, i.e., advance variable message sign (VMS) and LED lights, and road markings with pedestrian encircled. Each condition was tested with a yield/stop controlled marked crosswalk for two situations, i.e. with vs. without a pedestrian present. The experiment was conducted using the driving simulator at Qatar University. In total, 67 volunteers possessing a valid Qatari driving license participated in the study. Different analyses were conducted on vehicle-pedestrian interactions, driving speed, variations in acceleration/deceleration and lateral position. The results showed that both the LED and VMS conditions were helpful in increasing yielding rates up to 98.4 % and reducing the vehicle-pedestrian conflicts significantly. Furthermore, both treatments were effective in motivating drivers to reduce vehicle speed in advance. Considering the findings of this study, we recommend LED and VMS conditions as potentially effective solutions to improve safety at yield/stop controlled crosswalks.